Pertanggungjawaban Perusahaan Panas Bumi dalam Pelaksanaan K3LL pada Pemanfaatan Tidak Langsung Ditinjau dari Permen ESDM Nomor 33 Tahun 2021 Tentang K3LL dan Kaidah Teknik Panas Bumi - Andayani, Lily; Dwiprigitaningtias, Indah; Ikrardini, Zulfika (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The implementation of Occupational Safety and Health, Environmental Protection and Management (K3LL) is a fundamental obligation for every geothermal company, particularly in high-risk indirect utilization activities. The Minister of Energy and Mineral Resources (ESDM) Regulation Number 33 of 2021 establishes normative standards and technical rules that must be met by geothermal business operators, including the duty to conduct hazard identification, risk assessment, implement a K3LL Management System, and ensure sustainable environmental impact management. This research aims to analyze the geothermal company's liability in executing K3LL based on this regulation, and to examine the forms of administrative, civil, and criminal liability arising from violations or failures to fulfill K3LL obligations. The study employs a normative juridical method with a statutory and conceptual approach to examine the conformity of the company's K3LL implementation with the obligations stipulated in Permen ESDM 33/2021. The analysis also explores the relationship between geothermal technical rules, the principle of prudence, and the principle of environmental protection as the basis for legal liability. The results indicate that geothermal companies bear extensive and inherent legal responsibility, encompassing the obligation to ensure worker safety, prevent environmental pollution and damage, and guarantee compliance with technical standards throughout all stages of indirect utilization. Violations of K3LL obligations not only pose safety and environmental risks but can also lead to administrative sanctions (temporary cessation of activities, license revocation), up to criminal liability in the event of gross negligence resulting in environmental damage or fatalities. This research affirms that effective K3LL implementation is an integral part of sustainable geothermal industry governance and a strategic instrument for minimizing operational risks, strengthening environmental protection, and realizing a safe, efficient, and responsible utilization of geothermal energy.